Lyapounov stability for impulsive dynamical systems - Silva, Geraldo N. [UNESP]; Pereira, Fernando L. (Institute of Electrical and Electronics Engineers (IEEE), 2002)
This article addresses the problem of stability of impulsive control systems whose dynamics are given by measure driven differential inclusions. One important feature concerns the adopted solution which allows the consideration of systems whose singular dynamics do not satisfy the so-called Frobenius condition. After extending the conventional notion of control Lyapounov pair for impulsive systems, some stability conditions of the Lyapounov type are given. Some conclusions follow the outline of the proof of the main result.
Keywords: Algorithms; Availability; Control system analysis; Feedback control; Lyapunov methods; Problem solving; Control Lyapunov functions; Differential inclusions; Frobenius conditions; Impulsive dynamical systems; Lyapunov stability; System stability